Implementing 6G via Non-Terrestrial Networks (NTN): Considerations for High Altitude Platform Stations (HAPS) - Anicho, Ogbonnaya (Talenta Publisher, 2024)
Non-terrestrial networks (NTN) covering space-based and airborne network assets will be crucial for 6G delivery. Satellite constellations constitute a significant part of the NTN infrastructure but have certain limitations like long latency and Doppler shifts. High Altitude Platform Stations (HAPS) will complement the role of satellite systems and add significant value to the 6G NTN offering. This article draws the attention of the 6G development ecosystem to the need to prioritise HAPS studies and specifications. HAPS NTN will address three main factors relevant to 6G NTN deployments: Technology limitations of satellites, complexities of operations, automation and maintenance (OAM) and futureproofing 6G NTN. Wireless technologies change in 10-year cycles on average. However, intra-cycle changes (evolutions) also occur, further shortening the actual spans of the technology cycles. HAPS NTN can future-proof 6G NTN since it is retrievable for upgrades, retooling or redesign. Satellite systems will be highly exposed if these intra-cycle evolutions need hardware upgrades. Softwarisation and virtualisation would be helpful but do not eliminate the risk. This paper addresses the need to elevate the consideration for HAPS in 6G studies as it may serve as the ultimate technology guarantee for the success of 6G NTN.